La commémoration du Ve centenaire de la conquête du Mexique : premières approches sur la mémoire contemporaine d’un évènement lointain - Miriam Hernández Reyna (Caravelle)
This paper deals with memory’s sense and memorial politics that have arisen in Mexico during the Andrés Manuel López Obrador's administration since 2018. Based on the concept of memorial regime, we shall see that one of the actual politics’s singularities is the foundation of a public culture of repentance and the establishing of memory institutions which concern Colonial Era’s memory as well as Mexican national history.